2021
DOI: 10.21037/tau-21-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the learning curves of a novice and an experienced urologist for transrectal magnetic resonance imaging-ultrasound fusion prostate biopsy

Abstract: Background:The aim of the current study was to evaluate and compare the learning curves of transrectal magnetic resonance imaging-ultrasound fusion biopsy for two urologists with different backgrounds (Operator 1: experienced, self-trained and Operator 2: novice, trained by a mentor/MRI reading courses).Methods: A cohort of 400 patients who underwent fusion prostate biopsy in our department was analyzed.The learning curves were assessed in terms of overall and clinically significant prostate cancer (PCa) detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… 9 Novice readings have unreliable PIRADS diagnostic accuracy, with significant intra-reader improvement over time 10 . Management of equivocal PIRADS 3 lesions remains to be elucidated, with conflicting results in PCa detection reported for this ‘gray zone’ in PIRADS reading, with even more limited literature accessing correlation to radical prostatectomy (RP) pathology, complicating decisions for active surveillance or early intervention 11 , 12 , 13 . In this study, we evaluated the changes of PIRADS 3-5 histopathological outcomes over time based on RP specimens.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Novice readings have unreliable PIRADS diagnostic accuracy, with significant intra-reader improvement over time 10 . Management of equivocal PIRADS 3 lesions remains to be elucidated, with conflicting results in PCa detection reported for this ‘gray zone’ in PIRADS reading, with even more limited literature accessing correlation to radical prostatectomy (RP) pathology, complicating decisions for active surveillance or early intervention 11 , 12 , 13 . In this study, we evaluated the changes of PIRADS 3-5 histopathological outcomes over time based on RP specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Another important finding of this study is that the mean percentage of positive cores on TB increased from 18.1% to 44.2% over the 4-year study period. In a prospective study of 209 patients undergoing transrectal MRI/US fusion biopsy, Cata et al reported that the median percentage of positive cores on TB increased from 0% in the first 52 patients to 66.7% in the last 53 patients ( p = 0.06) [ 33 ]. In addition, Kasabwala et al retrospectively analyzed the accuracy and histological quality of MRI/US fusion biopsy in 173 patients and reported that the mean distance from biopsy trajectory to target decreased from 6.7 mm in tertile 1 to 0.06 mm in tertile 3 ( p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Mager et al retrospectively examined the TR fusion biopsy under sedo-analgesia of a novel and expert operators, reporting an improved detection and decreased time after 42 procedures, whilst Cata and coll. identified a detection plateau after 52 cases under LA [ 19 , 28 ]. Rosenzweig and coll.…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, we have investigated the LCs through several independent statistical methods on prospectively acquired data: CPGs fractions and medians trends, logistic/linear regression and CUSUM analyses; this overcomes the limitation imposed by arbitrarily defined group segmentation of other similar reports and enhances the robustness of our findings [ 19 , 28 ]. Our work is not devoid of limitations: no central MRI review was performed and heterogeneity in imaging was not assessed; the number of operators, their previous experience and the disease prevalence were different amongst included centres; the length of the biopsy series considered for each operator is limited, and therefore our results might reflect mainly the early phase of the learning curve; a single fusion biopsy platform (Esaote) was employed; no analysis on biopsy needle trajectory, percentage of tumour on positive cores, ratio of upgrading at final pathology was performed [ 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%